If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0.5(4x + -6) = -1 + 3x Reorder the terms: 0.5(-6 + 4x) = -1 + 3x (-6 * 0.5 + 4x * 0.5) = -1 + 3x (-3 + 2x) = -1 + 3x Solving -3 + 2x = -1 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -3 + 2x + -3x = -1 + 3x + -3x Combine like terms: 2x + -3x = -1x -3 + -1x = -1 + 3x + -3x Combine like terms: 3x + -3x = 0 -3 + -1x = -1 + 0 -3 + -1x = -1 Add '3' to each side of the equation. -3 + 3 + -1x = -1 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = -1 + 3 -1x = -1 + 3 Combine like terms: -1 + 3 = 2 -1x = 2 Divide each side by '-1'. x = -2 Simplifying x = -2
| 7/k-5=5/8 | | y+9=6x | | 3x^2-132+12=0 | | x-8/7=7/3 | | (x+4)+(x-3)+x=19 | | b+12.4=19.8 | | 7/a-8=8/2 | | 5x+3(2x-4)=43 | | 3v^2-2v-4=0 | | 2.5y+5= | | 9y-8y+3y= | | 18-(2x+8)=14 | | n-3n=13-4n | | -4y=-4x+10 | | n+5/7=2/3 | | 3x=y+11 | | 3.5+10m=7.98 | | 7r^2+6r+1=0 | | x+7/7=8/4 | | 16-9g=70 | | y=4-38-1.3 | | X+-z=yforz | | 3.5y+8= | | -4+x=3x+8 | | 2y=x-5 | | r^2-9r-12=0 | | -86-12=14a | | 5x-15+6=5x-9 | | 6.5x+3= | | -8x+5=37 | | 8(x+7)+5=8x+7 | | -10v=-5 |